Differential diagnostic value of plain CT scan in adrenal adenoma and non-adenoma: A two-center control study of mean attenuation value, minimum attenuation value, and CT histogram - Han, Zhijiang; Wu, Mengwei; Wei, Peiying; Zhu, Hanlin; Zhang, Xiaohan; Ding, Zhongxiang; Zhang, Ming (Frontiers in Endocrinology, 2022)
Objectives To investigate the value of mean attenuation value (AVmean), minimum attenuation value (AVmin), and CT histogram (CTH) for the differential diagnosis of adrenal adenoma and non-adenoma in two medical centers. Methods The plain CT data of 403 cases of adrenal adenoma and 141 cases of non-adenoma in center A were retrospectively analyzed, and compared with data of 86 cases of adenoma and 71 cases of non-adenoma in center B. All cases were confirmed by pathology or clinical follow-up. The diagnostic efficacy of AVmean ≤ 10 Hounsfield units (HU), AVmin ≤ 0 HU, and CTH negative pixels ≥ 10% for adrenal adenoma, and AVmin and CTH for adenoma with AVmean > 10Hu were compared between the two medical centers. Results In medical centers A and B, the AUC of AVmean for the differential diagnosis of adenoma and non-adenoma was 0.956 and 0.956, respectively, and the corresponding sensitivity, specificity, and accuracy were, 0.591 and 0.663, 1.000 and 1.000, 0.697, and 0.815, respectively, when the threshold was ≤ 10 HU. The AUC of AVmin was 0.941 and 0.958, respectively, and the corresponding sensitivity, specificity, and accuracy were 0.869 and 0.826, 0.986, and 0.972, 0.899, and 0.892, respectively, when the threshold was ≤ 0 HU. The AUC of CTH negative pixels was 0.948 and 0.952, respectively, and the corresponding sensitivity, specificity, and accuracy were 0.759 and 0.674, 1.000 and 1.000, 0.822, and 0.822, respectively, when the threshold was ≥ 10%. Among adenoma with AVmean >10 HU, the best threshold of AVmin in center A and center B were -0.250HU and 2.375HU, and the corresponding AUC, sensitivity and specificity were 0.858 and 0.846, 0.691 and 0.586, 0.986 and 0.958; the best threshold of CTH in center A and center B were 0.895% and 0.775%, and the corresponding AUC, sensitivity and specificity were 0.873 and 0.822, 0.818 and 0.724, 0.837 and 0.915. Conclusion AVmean, AVmin, and CTH are all important parameters for differentiating adrenal adenoma from non-adenoma. Even for adenomas with AVmean > 10 HU, AVmin and CTH still had high diagnostic efficiency. The three parameters are complementary, assisting clinicians to develop personalized treatments.